Lembu Sihat Enterprise / Shakib @ Muhammad Shakib Samsudin ... [et al.] - Samsudin, Shakib @ Muhammad; Syed Bakri, Sharifah Rosemiza; Che Hasan, Che Zaleha; Jaslee, Mohd Husaini; Suit, Suntina (Faculty of Computer and Mathematical Sciences, 2003)
After so many factors and risks have been taken into consideration, we have come to a conclusion about the most suitable business that we are going to perform. We named the business as Lembu Sihat Enterprise. From the name of our company, we can clearly predict the nature of the business. We are performing a manufacturing business that produce cattle milk as our major business. We distribute all the milk in two different ways. First, we distribute the milk directly to Jabatan Perkhidmatan Haiwan. This is to fulfill the requirement by Jabatan Perkhidmatan Haiwan in order to get all the benefit from them. Such benefits are ; monthly Veterinary services, subsidies and so forth. Secondly, we distribute the fresh milk directly to retail businesses. This transaction is done by consignment. Furthennore, we also manufacture yogurt as part of our business. From the daily production, we distribute 13% of the milk to the Yogurt Department to produce yogurt in two sizes; small and large. We perform the process of making yogurt by Rural Area Industry which is for the beginning, we just go for small. In order to increase the number of cattle that could be used to produce milk, we need to breed the existing cattle. Taking into consideration the probability that calf will also be produced, we have decided to sell all the calves of two months old to small cattle breeding businesses. This is considered a minor business for our company.